2010
DOI: 10.1111/j.1365-2109.2010.02693.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emerged shipment on the physiological condition of the adductor muscle in adult giant lion's paw scallop Nodipecten subnodosus (Sowerby 1835)

Abstract: Currently, there is an increasing interest in shipping live adult scallops to markets and broodstock to hatcheries; nevertheless, information about the shipping e¡ect on live scallops physiology is very scarce. In a previous study, a method in emersion was developed to ship scallop seed out of water, but it was not known whether this method is useful to transport adult organisms. As a consequence, the purpose of this study was to evaluate the e¡ects of transportation by the emersion method on the physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Evidence has suggested that such massive mortality is often associated with environmental changes (Zhang et al, 2015;Chen et al, 2016). Studies have shown that under the influence of salinity, temperature, pH and dissolved oxygen, physiological indicators, such as osmotic pressure, cellular immunity level, oxygen consumption and ammonia excretion, can be altered, resulting in physiological metabolism imbalance, growth inhibition and even death (Ghiselli et al, 2000;Nan et al, 2004;Liu and Yan, 2006;Ocaño-Higuera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has suggested that such massive mortality is often associated with environmental changes (Zhang et al, 2015;Chen et al, 2016). Studies have shown that under the influence of salinity, temperature, pH and dissolved oxygen, physiological indicators, such as osmotic pressure, cellular immunity level, oxygen consumption and ammonia excretion, can be altered, resulting in physiological metabolism imbalance, growth inhibition and even death (Ghiselli et al, 2000;Nan et al, 2004;Liu and Yan, 2006;Ocaño-Higuera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A series of research have been conducted, followed by evidence that environmental changes, such as salinity, pH, dissolved oxygen, temperature and so on, are often associated with such mortalities [28][29][30][31] . Physiologically, aquatic organisms are affected by changes in ammonia excretion rate, osmotic pressure, cellular immune level and oxygen consumption rate and so on, resulting in disturbance of basal metabolic balance, inhibition of growth and death in severe cases 28,29,[32][33][34] . Before large-scale farming of P. fucata, it is critical to identify the optimal conditions for such farms.…”
mentioning
confidence: 99%